Glaciological Data Collected by the 35th Japanese Antarctic Research Expedition during 1994-1995 - SHIRAIWA, Takayuki; SAITO, Takashi; SAITO, Takeshi; SHOJI, Hitoshi; TAGUCHI, Yuji; ABO, Toshihiro; YAMAMOTO, Yoshikatsu; INAGAWA, Yuzuru; YOKOYAMA, Kotaro; WATANABE, Okitsugu (National Institute of Polar Research, 1996)
P(論文) departmental bulletin paper